216k views
3 votes
Can you please help me on this question m+2m-6=-12+2m

2 Answers

0 votes

Answer:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

m+2*m-6-(-12+2*m)=0

Solve : m+6 = 0

Subtract 6 from both sides of the equation :

m = -6

ANSWER: m = -6

User James Warr
by
5.2k points
5 votes

Answer: m= -6

Explanation:

1st step: cancel 2m on both sides

m-6=-12

2nd step: Add 6 to both sides

m= -12+6

3rd Step Simplify -12+6 to -6

Answer: m= -6

User Amarnath Krishnan
by
5.0k points